Pendampingan Pembuatan E-Marketplace dan Laporan Keuangan pada UP2K "Mulan" Khususnya Dasa Wisma "Mawar" - Rahma Yuliani; Kasyful Anwar; Adisti Rahmatiasari (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2021)
Program Pengabdian Kepada Masyarakat in partner with Usaha Peningkatan Pendapatan Keluarga (UP2K) “Mulan” which consists of Dasa Wisma “Mawar” in the Kelayan Dalam, Banjarmasin city. Mitra is a Dasa Wisma community that has members from women who have micro businesses. The home-based businesses that are carried out by the Dasa Wisma women are in the form of dry and wet food products, including Sago Tempe Chips, Rengginang, Banana Chips, Betel Nut, Porridge Bingka, Rolls, Cakes, Resoles And Pies. Product sales are still carried out conventionally, namely deposited at a souvenir center shop, sold directly in traditional markets or receiving orders from certain parties, there are no records or bookkeeping, the production process still uses simple tools. Based on the analysis of the situation, the problems faced by partners are the partner marketing aspect regarding the e-marketplace, the financial aspect related to financial reports, and the production aspect is still being done with household appliances.Thus, the solution offered to solve partner problems is to conduct e-commerce socialization & training along with the preparation of financial reports. The activity method begins with the preparation stage, then the implementation stage, and finally the mentoring and reporting stage which is planned to be completed within a period of 8 months. The results after implementing the program have been achieved, namely, business actors have increased understanding of the importance of e-commerce, especially online marketing and understanding finances. In addition, partners who previously did not have a Shopee and Tokopedia account after the training already have an account registered with Shopee and can be used in business activities. Next partners are given a cash book so they can record costs and sales.